Advanced exergoeconomic evaluation of a new cryogenic helium recovery process from natural gas based on the flash separation – APCI modified process. (5th March 2018) - Ansarinasab, Hojat; Mehrpooya, Mehdi; Pouriman, Mohammadhosein
Highlights: Advanced exergoeconomic analysis is done on a new helium extraction process. Cost of exergy destruction and exergy destruction rate are calculated. Three different strategies are suggested to improve performance of the components. Abstract: An advanced method of exergoeconomic analysis was applied to a newly developed process configuration used for recovering helium from natural gas. In this process, a three stage propane refrigeration cycle is incorporated to provide a portion of the required refrigeration. Sensitivity analysis was also carried out for exergoeconomic factors and exergy destruction cost of the effective devices. In comparison with the existing processes, the proposed process has better performance in extracting the helium from the feed gas. Based on the results of conventional method, HE-105 and HE-104 heat exchangers have the highest extent of exergy destruction cost equal to 1889.68 /hr and 1263.58 /hr, respectively. The outcome of the advanced exergoeconomic analysis suggests that the exergy destruction cost (investment cost) of the compressors is avoidable while it is not true for the heat exchangers. Moreover, the exergy destruction costs induced from the remaining components are not considerable, thus the interactions among the process equipment is not strong.